Could coastal plants in western Amazonia be relicts of past marine incursions? - Bernal, Rodrigo (2019)
The rainforests of Amazonia comprise some of the most biologically diverse ecosystems on Earth. Despite this high biodiversity, little is known about how landscape changes that took place in deep history have affected the assembly of its species, and whether the impact of such changes on biodiversity can still be observed. Here, we present a hypothesis to explain our observation that plants typical of Neotropical coastal habitats also occur in western Amazonia, in some cases thousands of kilometres away from the coast. Evidence on their current distribution, dispersal biology and divergence times estimated from molecular phylogenies suggest that these plants may be the legacy of the large marine‐influenced embayment that dominated the area for millions of years in the Neogene. We hypothesize that coastal plants dispersed along the shores of this embayment and persisted as inland relicts after the marine incursion(s) retreated, probably with the aid of changes in soil conditions caused by the deposition of marine sediments. This dispersal corridor may also have facilitated the colonization of coastal environments by Amazonian lineages. These scenarios could imply an unexpected coastal source that has contributed to Amazonia's high floristic diversity and led to disjunct distributions across the Neotropics. We highlight the need for future studies and additional evidence to validate and shed further light on this potentially important pattern.